Molecular crosstalk between circadian clock and cancer and therapeutic implications - Qu, Meng (Frontiers in Nutrition, 2023)
The circadian clock governs the activity of many physiological processes, thereby playing a pivotal role in human health. Circadian disruption is closely associated with cancer development; in particular, recent discoveries have provided strong evidence supporting the specific functions of different molecular clock components in either promoting or inhibiting tumorigenesis. This narrative review aims to summarize the existing data on molecular connections between the clock and cancer. These results along with future efforts pave the road to targeting the circadian clock as a novel pathway for therapeutic intervention.